Fall in Foreign Exchange Reserves - Planning Commission (Planning Commission, 1958)
A drain on India s foreign exchange reserves began in April 1956 and has continued uninterruptedly ever since. By the end of March 1.957 despite a credit of Rs. 61 crores from the IMF. the reserves had fallen by Rs. 219 crores. The sterling balances at that date stood at Rs. 527 crores. Further losses since then had reduced them by the fourth week of September to Rs. 360 crores and it has been estimated that they may have fallen to about Rs. 260* crores by April 1958. 2. These foreign exchange difficulties are attributable to a rise in imports rather than to a fall in exports, which in fact have been somewhat higher than the Rs. 593 crores assumed in the Plan.
Government of India Planning Commission